Sidik Jari DNA Plasma Nutfah Mangga Berdasarkan Analisis Fragmen Marka SSR (Simple Sequence Repeat) Berlabel - Dwinita W. Utami; Tri J. Santoso; N. Hidayatun (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2012)
ABSTRACTDNA fingerprinting technology can be used for understanding the diversity of germplasm. The purpose of this preliminary study was to analyze the genetic diversity based on DNA fingerprints of mango germplasm using 15 fluorescent-labeled SSR markers. Nineteen Mango accessions from KP Cukurgondang collection, Pasuruan, East Java and 15 SSR markers for mangoes were used in this study. Development of multiplex sets of M13-labeled primer used in the analysis aimed at improving the effectiveness and efficiency of molecular marker technology in mango DNA fingerprint analysis. The analysis of genetic diversity of 19 accessions of mango germplasm using 15 SSR markers resulted in 7 groups where four groups separated from the other three. Each of the four groups consisted of one accession, while the three other groups consisted of some accessions. The results may represent the diversity of shape and color of fruit characters. However, further study is needed to get specific marker for each mango accession.Key word : DNA fingerprint, Mango, fluorescent SSR labeled.ABSTRAKTeknologi sidik jari DNA dapat digunakan untuk memahami keanekaragaman suatu plasma nutfah. Tujuan dari penelitian awal ini adalah menganalisis keragaman genetik berdasarkan sidikjari DNA plasma nutfah mangga menggunakan 15 marka SSR yang berlabel fluorescent. Sembilan belas aksesi plasma nutfah mangga dari koleksi KP Cukurgondang, Pasuruan, JawaTimur dan 15 marka SSR untuk mangga digunakan dalam penelitian ini. Pengembangan set multiplex primer berlabel M13 digunakan dalam analisis bertujuan untuk meningkatkan efektivitas dan efisiensi teknologi marka molekuler dalam analisis sidikjari DNA mangga. Analisis keragaman genetik 19 aksesi plasma nutfah mangga menggunakan 15 marka SSR dapat menghasilkan 7 kelompok yang terdiri atas 4 kelompok yang masing-masing beranggotakan satu aksesi dan 3 kelompok lainnya yang terdiri atas beberapa aksesi. Hasil pengelompokan dapat mewakili keragaman karakter bentuk dan warna buah. Namun demikian perlu dilakukan analisis lebih lanjut untuk mendapatkan penciri spesifik masing-masing aksesi plasma nutfah mangga.Kata kunci : Sidikjari DNA, mangga, SSR berlabel fluorescent